Fucoidan-coated silica nanoparticles promote the differentiation of human mesenchymal stem cells into the osteogenic lineage - Amorim, Sara (2023)
Silica nanoparticles (SiNPs) are widely used in biomedical applications, such as cancer therapy/diagnosis or tissue engineering and regenerative medicine. Herein, we synthesized SiNPs and modified them with sulfonic acid groups (by organosilylation followed by oxidation) or a sulfated polysaccharide (i.e., fucoidan, a seaweed biopolymer, by using electrostatic surface immobilization) due to the known capacity of the sulfonic/sulfate moieties to stabilize proteins and promote stem cell differentiation toward the osteogenic lineage. The developed pristine and functionalized nanoparticles were characterized by dynamic light scattering (DLS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS), showing the monodisperse size distribution (between 360 and 450 nm) and the success of the coating/functionalization with fucoidan or sulfonic groups. The developed SiNPs (at a concentration of 50 Î¼g/mL) were assessed through their contact with SaOs2 cells evidencing their cytocompatibility. Furthermore, the osteogenic differentiation of bmMSCs was evaluated by the quantification of ALP activity, as well as the expression profile of osteogenic-related genes, such as Runx2, ALP, and OP. We found that the coating of the SiNPs with fucoidan induced the osteogenic differentiation of bmMSCs, being an effective mediator of bone regeneration.